1996
DOI: 10.1152/ajprenal.1996.270.5.f756
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A treatment induces overexpression of P-glycoprotein in the kidney and other tissues

Abstract: To see whether P-glycoprotein (PGP) expressed in renal brush-border membranes (BBM) could interact with compounds known as modulators of multidrug resistance (MDR), photoaffinity-labeling experiments were performed. A 145k-Da protein was photolabeled with [125I] iodoarylazidoprazosin, and this labeling was reduced in the presence of cyclosporin A (CsA) and PSC-833 (PSC). Interaction of CsA with PGP was further investigated by treating rats with daily subcutaneous injections of CsA (10 mg.kg-1.day-1). After thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 0 publications
2
60
1
Order By: Relevance
“…16,18 In this study, oxycodone had an efflux ratio of 2.06 that was decreased to 1.01 by verapamil, and significantly higher oxycodone brain levels were observed for mdr1a/b (−/−) versus mdr1a/b (+/+) mice. Finally repeated administration of oxycodone resulted in upregulation of P-gp and also affected the accumulation of the well-known P-gp substrate, paclitaxel in the liver, kidney, and brain tissues of oxycodone tolerant rats.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…16,18 In this study, oxycodone had an efflux ratio of 2.06 that was decreased to 1.01 by verapamil, and significantly higher oxycodone brain levels were observed for mdr1a/b (−/−) versus mdr1a/b (+/+) mice. Finally repeated administration of oxycodone resulted in upregulation of P-gp and also affected the accumulation of the well-known P-gp substrate, paclitaxel in the liver, kidney, and brain tissues of oxycodone tolerant rats.…”
Section: Discussionmentioning
confidence: 56%
“…4,6,15,38 P-gp substrates such as morphine, cyclosporin A, vincristine, dexamethasone, and rhodamine 123 are known to induce the level of expression of P-gp upon chronic administration. 16,18 As such, it would be expected that repeated administration of P-gp substrates that are opioid agonists will markedly increase the P-gp expression. In fact, when morphine was administered to Sprague Dawley rats, a twofold increase in brain P-gp expression was observed in morphine-treated rats when compared to saline-treated rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, del Moral et al suggested that variability in local P-glycoprotein expression is important for chronic CNI nephrotoxicity by using immunohistochemistry and Western blotting in a rat model of chronic CNI nephrotoxicity (286). Another study in rats showed that exposure of cultured renal tubular cells to cyclosporine induces P-glycoprotein overexpression (287). In addition, del Moral et al demonstrated that the up-regulation of P-glycoprotein was inversely related to the incidence of arteriolar hyalinosis, interstitial fibrosis, and periglomerular fibrosis (286).…”
Section: Local Renal Exposure To Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…31 This may also be a potential mechanism for the induction of multidrug resistance through PGP upregulation. To complicate matters further, (a) induction of PGP by drugs is tissue-dependent, and this may have some bearing upon the relevance of particular inducers in the study of drug resistance in different diseases 32 ; and (b) it is also possible that baseline or constitutive expression levels may determine the maximal degree of induction that occurs in response to contact with an environmental inducer. Furthermore, the extent of induction of proteins by drugs is frequently dose-dependent and therefore differences in intracellular concentrations of inducing drugs between individuals may contribute to differences in PGP expression levels.…”
mentioning
confidence: 99%